2023
DOI: 10.3390/d15020229
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Abundance, Density and Distribution of Cetaceans in the Bulgarian Black Sea Shelf in 2017

Abstract: Black Sea cetaceans are isolated and nominated as endemic subspecies listed in the IUCN Red List of Endangered species: the harbour porpoise and bottlenose dolphin as Endangered (EN) and the common dolphin as Vulnerable (VU). Studies of their distribution and abundance are scarce but obligatory for assessment of their conservation status. Being highly mobile apex predators entails large variations in spatial and temporal distribution. Two vessel line–transect distance sampling surveys were conducted in 2017 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Elsewhere, acoustic approaches such as ADDs (pingers) have been used (Dawson et al, 2013). A few models have been tested in Türkiye, Romania and Bulgaria, some showing good results while others not (Gönener and Bilgin, 2009;Popov et al, 2020). In the current study, use of PAL pingers showed promising results.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…Elsewhere, acoustic approaches such as ADDs (pingers) have been used (Dawson et al, 2013). A few models have been tested in Türkiye, Romania and Bulgaria, some showing good results while others not (Gönener and Bilgin, 2009;Popov et al, 2020). In the current study, use of PAL pingers showed promising results.…”
Section: Discussionmentioning
confidence: 63%
“…Three models of pingers have been tested: Future Oceans 10 kHz, Future Oceans 70 kHz and Porpoise Alerting Devices (PAL), frequency 10 kHz. Observed differences in bycatch levels in strings fitted with Future Oceans pingers and those without pingers were not significant in 2019 (Popov et al, 2020). The only model which showed significant decrease in bycatch (86%, p<0.05) was the PAL pinger deployed on six strings.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Monitoring surveys in the Black Sea have been limited, with most large-scale surveys conducted prior to 1987. Recent efforts have focused on local surveys in coastal areas (Birkun et al, 2004, Birkun et al, 2004Dede and Tonay, 2010;Birkun et al, 2014Kopaliani et al, 2015Panayotova and Todorova, 2015;Gladilina and Gol'din, 2016;Gladilina et al, 2017;Popov et al, 2017;Baș et al, 2019;Paiu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%